Constructing advanced dielectric elastomer based on copolymer of acrylate and polyurethane with large actuation strain at low electric field. (1st August 2018) - Zhao, Yu; Zha, Jun-Wei; Yin, Li-Juan; Li, Sheng-Tao; Wen, Yong-Qiang; Dang, Zhi-Min
Abstract: Dielectric elastomers (DEs) are kinds of advanced functional materials, attracting more attention due to that they can used to fabricate ingenious devices. In this work, a series of advanced DEs based on the copolymer of polyurethane (PU) and acrylate, were chemically prepared through the condensation polymerization between p (BA-HEA), the n -butyl acrylate (BA) and hydroxyethyl acrylate (HEA) copolymer and diphenyl methane diisocyanate (MDI), named as p (BA-HEA)@MDI. The absence of urethane group was confirmed by infrared spectroscopy measurements. And the DEs show a decreased elastic modulus and an improved elongation at break with the decreasing content of MDI. For the absence of strong polar urethane group, the dielectric permittivity of new DEs still keeps at a relatively high value. And the p (BA-HEA)@MDI-3 shows the highest electromechanical sensitivity and the foreseeable highest actuation strain (14.4%) at a relatively low electric field (15.2 kV/mm) without any pre-strains, which is almost 2 times of that of VHB 4910 (acrylic adhesive tape, 3 M Corporation). The present work provides a new strategy to design high performance dielectric elastomers. Graphical abstract: Image 1 Highlights: Series of advanced DEs based on the copolymer of polyurethane and acrylate, were prepared through a simple method. The performance of the advanced dielectric elastomer can be tuned by adjusting its ingredient. The advanced dielectric elastomers can display high actuated strain at a very low driving electric field.